Corpses of Metaphor. Images of Death in David Leavitt and Jamaica Kincaid (Altre Modernità, 2010)
This essay analyzes two works, My Brother by Jamaica Kincaid, and "Saturn Street" by David Leavitt, investigating the construction of homosexuality as a process accomplished by resorting to illness (AIDS) and death. In both works, indeed, the slow and dramatic course of AIDS amounts to the progressive unveiling of homosexuality as a social threat or a cause of anxiety and repulsion. The two works are set in different contexts: whereas Jamaica Kincaid refers to the problematic situation of homosexuality in the Caribbean, David Leavitt explores the social and cultural scenario of the 1990s Los Angeles, in the wake of a by now ended utopian confidence in science and technology.  This comparative approach helps us understand the political dynamics through which, in different and, to some extents, opposite realities, the social stigma of AIDS worked as a means to construct homosexual identity and set it apart from the sanitized spectrum of normal and sanctioned sexual behaviors. The point I want to make in this essay is that the corpse is used as an effective metaphor for a dehumanized depiction of male homosexual and ill subjects.